Learning More Effectively: Developing And Utilizing Non-Print Media: Transparency, Audio, And Audio Transparency - Dessani, Yulia; Fitri, Nabila Aulia; Sakdiyah, Sakdiyah; Dzikrullah, Muhammad; Suryadi, Fathurrahman; Fatimah, Fatimah (Khalaqa: Journal of Education and Learning, 2025)
The background of this study is the need for more effective learning strategies through the development and utilization of non-print media, namely transparencies, audio, and audio transparencies, in Islamic Religious Education (PAI) learning. Traditionally, PAI learning has been monotonous and reliant on a single medium, leading to a lack of student interest and a decline in learning motivation. Therefore, this study aims to explore the implementation, development, and utilization of non-print media that are more effective and relevant to students' current needs. The research method used is library research with a qualitative approach, in which various literatures related to non-print media (transparencies, audio, and audio transparencies) are actively analyzed to determine their relevance and effectiveness in the context of PAI learning. Non-print media (transparencies, audio, and audio transparencies) help students understand Islamic teachings through concrete examples, allow them to actively engage in learning related to Islamic values, and provide opportunities for students to develop their potential in a more in-depth manner. The findings of this study indicate that the use of non-print media (transparencies, audio, and audio transparencies) in PAI learning not only enhances students' understanding of PAI material but also strengthens their engagement and motivation in the learning process.